(untitled) (Research, Society and Development, 2021)
This study aims to describe the work process of the extended family health and primary care nucleus, with an emphasis on group practices developed by professionals from the extended family health and primary care nucleus. This is an integrative review based on advanced research of studies in databases: SCIELO, PubMed and LILACS, using the Boolean operators AND and OR, using the keywords: NASF, collective activity, continuing education, education in health and group practice. Articles published in Portuguese that portrayed the respective theme were included, between the periods 2011 to 2021, and those older than ten years old, that were not available for free and those that were not associated with this theme, monographs, dissertation, theses, were excluded. abstracts and duplicate articles. 09 articles were selected according to the previously established inclusion criteria. Groups with a wide variety of target audiences were identified. It is concluded that the group practices carried out by the teams of the Expanded Family Health Center can benefit countless people, with the possibility of developing groups in different areas and themes according to the specific needs of each population. However, the search for articles was difficult, due to the fact that numerous authors only cited the development of the groups, without detailing their purpose and what activities were carried out in each group, leaving a gap that hinders and compromises the understanding of the work process of the expanded nucleus of family health and primary care, within the scope of therapeutic/educational groups.